Factors Influencing Brand Switching Behaviour on Telecommunication Industry in Nepal - Manandhar, Raju Bhai (Nepal Journal of Multidisciplinary Research, 2021)
Consumer switching behaviour is the process showed by a consumer, behaving differently to particular brand and alteration in the preference of existing product or service. Brand switching occurs when a consumer switches their allegiance from one brand of certain type of product to another brand. In the general, consumer satisfaction is found to be the most common factor responsible for consumer’s switching action. The main purpose of the study is to explore the factors influencing the brand switching behaviour on the telecommunication industry in Nepal. The study is based on the descriptive research design. The sample selected for the study is on the basis of judgmental and convenience sampling. The survey questionnaire is designed to generate the primary data. Those participants were only included for the questionnaire survey who have sufficient time and are willing to participate. A structured questionnaire was administered to 60 customers of telecommunication industry in Nepal. The statistical tools used in this study to analyze the data. As per the result of ranking question, service quality was ranked most important influencing factor for brand switching, competitive offers were ranked second important factor, while price was ranked comparatively less important factor among the three. The study has included limited variables whereas other factors such as switching cost, brand image, transparency, etc. have also impact on the brand switching behaviour so future researcher can study including these variables among the larger sample size to get more realistic result in brand switching behaviour.